Make : ultimate guide to 3D printing - Frauenfelder, Mark (Maker Media, 2013)
It's 3D Printing: The Next Generation! The technology's improving, prices are dropping, new models are hitting the market, and 3D printers are appearing on desktops, workbenches, lab shelves, and kitchen tables all over the world. Not only are we seeing better, faster, and cheaper 3D printers, we're also seeing new printing materials, easier-to-use design software, powerful scanning technology, and the rise of an entire ecosystem of 3D peripherals and services that support 3D printing technology. Make's second annual 3D Printing Guide is once again your go-to resource for discovering the latest information in this fast-changing field of printers, software, projects, and accessories. Inside, you'll find up-to-date reviews on the latest in 3D printing technology, feature and model comparisons, tutorials and stories about 3d printing, and some of the coolest 3d printed objects out there.